Asphyxia risk factors in adult psychiatric wards. Issue 3 (26th February 2020) - Sugisawa, Satoru; Nozue, Shinji; Kurihara, Tatsuya; Koya, Hiroaki; Tsuneoka, Toshiaki; Nagai, Tsutomu; Kurata, Naomi; Inamoto, Atsuko; Takahashi, Koji; Sasaki, Tadanori
Abstract: Purpose: To identify factors for choking in psychiatric wards that can be easily screened. Design and Methods: Data were collected from patients admitted to the acute phase psychiatric wards who were assessed for swallowing function by dentists. We defined 47 and 102 patients of choking in the high‐ and low‐risk groups, respectively. Findings: Through multivariate analysis, we identified basal metabolic index and two Drug‐induced Extra‐pyramidal Symptoms Scale items, bradykinesia and tremor, as independent choking factors. Practice Implications: Choking risk is related to patient tolerability rather than to the absolute severity of psychiatric symptoms or psychotropic dose.